Molecular Identification of AHPND Positive Vibrio Parahaemolyticus causing an outbreak in South-West Shrimp Farming Regions of Bangladesh - Eshik, Md Mostavi Enan; Abedin, Md Minhazul; Punom, Nusrat Jahan; Begum, Mst Khadiza; Rahman, Mohammad Shamsur (Journal of Bangladesh Academy of Sciences, 2018)
Acute hepatopancreatic necrosis disease (AHPND) of shrimps is a bacterial disease, first appeared in China in 2009 and causes mortality up to 100 % which usually occurs early (within approximately first 35 days) after stocking shrimp fry of black tiger shrimp, Penaeus monodon (Fabricius) and white leg shrimp, Litopenaeus vannamei (Boone). The purpose of this study was to isolate and identify the pathogenic strain of V. parahaemolyticus causing AHPND in cultured shrimps (P. monodon) using molecular techniques. After a disease outbreak in April 2017, shrimp samples were collected from three different locations of south-west shrimp farming region of Bangladesh viz. Satkhira, Khulna and Bagerhat districts. In this study, three selective media were used for primary isolation of V. parahaemolyticus. Among 28 primary isolates, representative14 isolates were checked for the species-specific detection of V. parahaemolyticus using ldh primers and all of them were found to be positive. The isolates were further characterized to check their AHPND positivity using AP3 and AP4 primers. Four isolates showed positive results for both AP3 and AP4 which indicated that the isolates were AHPND positive. This study also report that all AHPND positive strains showed sensitivity to the antibiotics Tetracycline and Nalidixic Acid. The results of this study will help the farmers and policy makers to make plan to protect shrimps from AHPND and thereby sustain the shrimp farming in Bangladesh. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 127-135, 2017